AB0621 The timing of urinary protein creatinine ratio normalization in patients with ln treated with mycophenolate mofetil (MMF) as their first line therapy. (23rd January 2014) - Timlin, H.; Fang, H.; Magder, L.; Petri, M.
Abstract : Objectives: Mycophenolate mofetil (MMF)has become the primary induction therapy for lupus nephritis (LN). The purpose of this study was to look at the timing of the protein creatinine ratio reaching 500mg after starting Mycophenolate mofetil (MMF) for class III, IV or V lupus nephritis. Methods: 21 SLE patients began mycophenolate mofetil (MMF) shortly after a biopsy-confirmed diagnosis of LN. The baseline urine protein ranged between 0.635 to 11.91grams, with only 1 patient being below 1 gram at baseline. They consisted of 18 females, 3 males, 9 African Americans, 8 Caucasians, and 4 other ethnicities. Ages ranged from 18 to 70 with a mean age of 37 (SD=15).The mycophenolate mofetil (MMF) dose ranged between 250 to 3000 mg per day. We estimated the survival function time until the urine protein reached 0.5 grams or less after starting mycophenolate mofetil (MMF) using an approach that accommodates interval censored data. Results: The graph shows an estimate of the probability that patients would still have urine protein above 500 mg by various time points after starting mycophenolate mofetil (MMF). We estimate that 50% of patients will have reached 0.5 grams of protein with 51 days of starting mycophenolate mofetil (MMF), and 77% will have reached 0.5 grams within 180 days. Conclusions: This study demonstrates that the majority of patients with lupus nephritis (77%) can reach a urine protein creatinine ratio of 0.5 grams or less by 6 months after initiation of mycophenolate mofetil (MMF). These data can be used to determine sample sizes for clinical trials in lupus nephritis; but also suggest that a more stringent goal should be considered. Disclosure of Interest: None Declared